2010
DOI: 10.1038/sc.2010.100
|View full text |Cite
|
Sign up to set email alerts
|

Secondary complications and subjective well-being in individuals with chronic spinal cord injury: associations with self-reported adiposity

Abstract: Study design: This is a cross-sectional study. Objectives: To examine the associations between adiposity, secondary complications and subjective well-being (SWB) in individuals with spinal cord injury (SCI). Results: Controlling for covariates, individuals who reported being overweight were more likely to have a history of overuse injuries and fatigue, experienced a greater impact of overuse injuries and fatigue, had greater pain and depressive symptoms, and had lower satisfaction with life than individuals wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…Their deleterious effects impact quality of life, 21 their prevalence tends to increase over time, 22 and there are potential interactions between some complications (eg, being overweight is more likely to lead to upper limb overuse and fatigue) that may affect life satisfaction. 23 The high prevalence of SHCs reported in the survey is of concern. This prevalence is comparable to that in studies in the early 1990s 24 and more recently in Canada, 22,23 including studies reporting a high prevalence of pain in various countries [25][26][27] (NT lesion).…”
Section: Secondary Health Conditionsmentioning
confidence: 95%
See 1 more Smart Citation
“…Their deleterious effects impact quality of life, 21 their prevalence tends to increase over time, 22 and there are potential interactions between some complications (eg, being overweight is more likely to lead to upper limb overuse and fatigue) that may affect life satisfaction. 23 The high prevalence of SHCs reported in the survey is of concern. This prevalence is comparable to that in studies in the early 1990s 24 and more recently in Canada, 22,23 including studies reporting a high prevalence of pain in various countries [25][26][27] (NT lesion).…”
Section: Secondary Health Conditionsmentioning
confidence: 95%
“…23 The high prevalence of SHCs reported in the survey is of concern. This prevalence is comparable to that in studies in the early 1990s 24 and more recently in Canada, 22,23 including studies reporting a high prevalence of pain in various countries [25][26][27] (NT lesion). 28 Sexual dysfunction was also reported to be a major issue, 29 affecting social participation and quality of life, and is one of the most deleterious complications for many people with SCI.…”
Section: Secondary Health Conditionsmentioning
confidence: 95%
“…In persons with SCI in the chronic phase, fatigue has been shown to relate to age 10 and lesion characteristics. 4 With regard to physical factors, being overweight has been found to negatively impact fatigue, 11 and physical activity that requires a lot of physical effort 12 is related to less fatigue in persons with SCI in the chronic phase.…”
Section: Introductionmentioning
confidence: 99%
“…1 The first version of the International SCI Core Data Set 1 has been the adopted standard for collecting and reporting minimal data on study population characteristics and has demonstrated its applicability globally. [2][3][4][5][6][7][8][9] All International SCI Data Sets are scheduled to undergo periodic review and revision when new knowledge and experience is gained to ensure continued relevance, acceptance and usage by the SCI clinical and research community. 10 The revisions agreed upon by consensus are summarized in this manuscript.…”
Section: Introductionmentioning
confidence: 99%